Anticiper la route : étude de cas dans l’est de la Guyane française - Sandra Nicolle; Madeleine Boudoux d’Hautefeuille (VertigO)
The construction of roads in Amazonia raises very specific questions in the research of sustainable development. If they are indeed considered by public policies developed in this region as one of the main tool for economic development, they are also highly criticized on the environmental (deforestation) and socio-economic levels. The opening of roads in French Guiana, a French Overseas territory located in Amazonia, is therefore a big responsibility for the French government. The impact study is one of the procedures allowing to assess a priori the environmental and socio-economical impacts of a road infrastructure project on a given territory, and to suggest adequate measures in relation to these positive or negative impacts. The publication of this study is the only time when the public can give its opinion on the project. This paper thus provides a partial ex post evaluation of the efficiency of environmental and socio-economic ex ante assessments in the case of a national road construction (RN2), analyzing their specificities and margins of improvement specific to this area.